wp 2010
DOI: 10.24149/wp1002
|View full text |Cite
|
Sign up to set email alerts
|

Credit, Housing Collateral and Consumption: Evidence from the U.K., Japan and the U.S.

Abstract: The consumption behaviour of UK, US and Japanese households is examined and compared using a modern Ando-Modigliani style consumption function. The models incorporate income growth expectations, income uncertainty, housing collateral and other credit effects. These models therefore capture important parts of the financial accelerator. The evidence is that credit availability for UK and US but not Japanese households has undergone large shifts since 1980. The average consumption-to-income ratio shifted up in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 66 publications
5
40
0
Order By: Relevance
“…Housing markets with stronger bank balance-sheet exposure show stronger housing return linkages. We have shown that bank integration can not15 The effects for the US and UK are consistent withAron et al (2012) who assess differences in housing wealth effects across Japan, the UK, and the US. only add additional information next to other spatial linkages -such as trade, FDI, geographic proximity, etc.…”
supporting
confidence: 78%
“…Housing markets with stronger bank balance-sheet exposure show stronger housing return linkages. We have shown that bank integration can not15 The effects for the US and UK are consistent withAron et al (2012) who assess differences in housing wealth effects across Japan, the UK, and the US. only add additional information next to other spatial linkages -such as trade, FDI, geographic proximity, etc.…”
supporting
confidence: 78%
“…Mortgage equity withdrawals (MEWs) supported consumption booms in the UK (Miles, 1992;and Muellbauer and Murphy, 1997) and US (Aron et al, 2012;Greenspan and Kennedy, 2008;Hurst and Stafford, 2004;andSufi, 2010, 2011). At the macro-level, MEWs are positively correlated with an increased sensitivity of consumption to housing wealth (Duca, 2006;Carroll et al, 2011) and at the micro level, with liquidity constraints (Benito, 2009;Browning et al, 2008;Hurst and Stafford, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…33 Office for National Statistics, 2006. 34 This is implied but not explicitly stated by Aron et al (2012). I am very grateful to John Muellbauer for extracting this estimate for me.…”
Section: The 1980smentioning
confidence: 86%
“…32 But this was also a supply-side reform that had a major short-term impact on the growth of aggregate demand, working in particular through the household savings ratio, which fell by about 7 percentage points between 1980 and 1987. 33 Econometric analysis by Aron et al (2012) that takes into account the direct and indirect (through house prices and household debt) implications of the change in credit conditions facing consumers suggests that financial liberalisation raised consumer spending by an amount equivalent to at least 3.5 per cent of GDP in 1987. 34 31 Cobham, 2002.…”
Section: The 1980smentioning
confidence: 99%